Bijak Dalam Pengelolaan Keuangan Dan Gizi Keluarga - Siti Nur Azizah (JCSE: Journal of Community Service and Empowerment, 2023)
The household economy as the smallest part of the economic system must be managed properly so that the goal is to improve the welfare of all family members. This service was carried out in Candiwulan Adimulyo village for PKK members who are housewives to increase their knowledge about household income management. It is expected that housewives will keep records and make priority scales in grouping expenses and motivate them to increase their income by selling snacks or working informally.